A Randomised Comparative Clinical Study to Evaluate the Efficacy of Sadhyovirechana with Gandharvahastadi Eranda Taila followed by Agnilepa and Dhanyamla Dhara in the Management of Amavata (AYUSHDHARA, 2024)
Amavata is a Kruchrasadya vyadhi caused due to formation of Ama, vitiation of Vata and Agni vaishamya. Madhavakara mentions it as a ‘Sa kashtah sarva roganam’. Amavata is an Ama pradhana vyadhi, it requires Ama pachana as primary management. Hence in the present study, Sadhyovirechana as Abhyantara Shodhana Chikitsa followed by Bahya chikitsa in the form of Agnilepa and Dhanyamla Dhara in two different groups were used to evaluate their efficacy in the management of Amavata. Aims and Objectives: 1. To evaluate the efficacy of Sadhyovirechana with Gandharvahastadi Eranda Taila followed by Agnilepa in Amavata. 2. To evaluate the efficacy of Sadhyovirechana with Gandharvahastadi Eranda Taila followed by Dhanyamla dhara in Amavata. 3. To compare the efficacy of both the groups in Amavata. Methods: This is a comparative clinical study with pre-test & post-test design where in 40 patients diagnosed with Amavata of either sex were randomly assigned into two groups viz., Group A & Group B. Intervention: Group A: Sadhyovirechana on 1st day followed by Agnilepa for next 7 days. Group B: Sadhyovirechana on 1st day followed by Dhanyamla Dhara for next 7 days. Results: The effect of the treatment in both the groups were assessed by applying Wilcoxon’s rank sum test within the groups and Mann-Whitney U test between the groups, it showed that Group A showed better results than Group B. Conclusion: It can be concluded from the study that in the management of Amavata, Sadhyovirechana followed by Agnilepa and Dhanyamala Dhara Chikitsa drugs and procedures of both the groups are highly effective in treating Amavata.